Analisis Potensi Pembangkit Listrik Tenaga Mikrohidro (PLTMH) Pada Sungai Air Besar Kampung Air Besar Kabupaten Fakfak - Yulianto La Elo; Rusliadi Rusliadi; Zharin Fahrah Syahdinar (Universitas Darul Ulum, 2023)
Fakfak Regency, West Papua Province has a Watershed and Waterfall, the Air Besar River is one of the rivers that has the opportunity to be used as a Micro Hydro Power Plant (PLTMH). Due to the large difference in flow elevation between upstream and downstream, it is hoped that this local resource can be developed for other potentials, one of which is for Micro Hydro Power Plants (PLTMH). It is hoped that this Micro Hydro Power Plant (PLTMH) will not only be able to use water as a source of energy, but also increase profits with the availability of tourism. The purpose of this research is to detect the ability of the Air Besar River as a Micro Hydro Power Plant (PLTMH). The research method used is the floating method to determine the water rate and the cross section. Furthermore, calculations are carried out to obtain the amount of water discharge, determining the effective fall height (Heff) of the flow to obtain power and energy that can be produced by river flow while account the efficiency of the generator and turbine. From the calculation results, it is known that the large water discharge from the river is 23,826 m3/s, the effective fall height (Heff) flow is 4 m. From the results of these calculations, it is known that the estimated electrical power that can be generated is 620.8159 kW.